Revisiting the future - Dooley, Jeffrey (Michaelis School of Fine Art, 2015)
Revisiting the future re-examines some ideas of the Italian Futurist painters Boccioni, Balla, Carra, Russolo and Severini. These ideas included multiplied sensations and states of mind, interpenetration and superimposition, lines of force, and placing the spectator at the center of the painting. These ideas are then examined in relation to the senses and to contemporary art practice. I present ideas on how images for the various senses can operate both individually and collectively to create interactive, multi-sensory communication surfaces. The works I produced are my response to the challenges posed to painting and artistic practice by the sensorium and the Futurist painters' ideas.